2019
DOI: 10.5694/mja2.50052
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐exposure prophylaxis forHIVprevention during pregnancy and lactation: forget not the women and children

Abstract: Summary Pregnancy is known to be a time of increased susceptibility to acquiring to human immunodeficiency virus (HIV) infection and this increased maternal risk places the unborn child at risk of vertical transmission. Pre‐exposure prophylaxis (PrEP) involves the provision of antiretroviral therapy to an HIV‐negative individual with ongoing risk of HIV exposure to limit the likelihood of HIV transmission. The inclusion of PrEP as part of a comprehensive strategy is recognised as an effective and safe means … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Individuals may be at an increased risk for HIV infection during pregnancy, and HIV transmission in pregnancy is associated with an increased risk of perinatal transmission, emphasizing the importance of HIV prevention during preconception and pregnancy. 22,40,41 The 2 clinical trials that demonstrated the efficacy of PrEP in women, the Partners Pre-Exposure Prophylaxis trial (Partners PrEP) and Botswana TDF2 Trial (TDF2), discontinued the use of PrEP among participants who incidentally became pregnant during the trials. 15,32,38 In the TDF2 trial, there was no difference in the rate of fetal loss (7.1% with TDF/FTC, 6.9% with placebo; P = 1.00) in early pregnancy between participants who received TDF/FTC compared with those who received placebo.…”
Section: Prep During Pregnancy and Lactationmentioning
confidence: 99%
“…Individuals may be at an increased risk for HIV infection during pregnancy, and HIV transmission in pregnancy is associated with an increased risk of perinatal transmission, emphasizing the importance of HIV prevention during preconception and pregnancy. 22,40,41 The 2 clinical trials that demonstrated the efficacy of PrEP in women, the Partners Pre-Exposure Prophylaxis trial (Partners PrEP) and Botswana TDF2 Trial (TDF2), discontinued the use of PrEP among participants who incidentally became pregnant during the trials. 15,32,38 In the TDF2 trial, there was no difference in the rate of fetal loss (7.1% with TDF/FTC, 6.9% with placebo; P = 1.00) in early pregnancy between participants who received TDF/FTC compared with those who received placebo.…”
Section: Prep During Pregnancy and Lactationmentioning
confidence: 99%
“…The decrease in consistent condom use among gay and bisexual men since the introduction of pre‐exposure prophylaxis has led to an increase in the burden of bacterial STIs, particularly rectal chlamydia infections, and warrants attention . Pre‐exposure prophylaxis guidelines for pregnant and lactating women should also be prioritised to ensure that a range of safe and effective options are available to reduce the vertical transmission of HIV …”
Section: Hiv and Sexually Transmitted Infectionsmentioning
confidence: 99%